SiO2 nanofiber reinforced P(VdF-HFP) based microporous polymer electrolytes for advanced energy storage applications - Borah, Sandeepan; Saikia, Lakshi; Guha, Ankur K.; Deka, M. (Colloids and surfaces. A, Physicochemical and engineering aspects, 2023)
The application of ceramic nanofiller-dispersed microporous polymer gel electrolytes (MPGEs) in energy storage devices has been a subject of utmost research importance for a long time. However, a clear understanding of ion transport properties in this type of electrolyte is not yet achieved. The present article includes a detailed investigation of the uptake kinetics and ion transport mechanism in poly(vinylidene fluoride-co-hexafluoropropylene) [P(VdF-HFP)] based MPGEs reinforced with silica (SiO2) nanofibers. Very high ionic conductivity of 9.21 × 10−3 Scm−1 at ambient temperature has been achieved at a relatively low uptake ratio of 212 %, maintaining the dimensional integrity of the films when nanofiber content in P(VdF-HFP) is 2.5 wt%. This result ascertains the role of nanofibers in promoting ion transport in MPGEs, as revealed by XRD, FTIR, XPS, and simulative computational studies. The diffusive behavior of the MPGEs has been analyzed for both the liquid and the gel phases of the porous polymer membranes. The maximum diffusion coefficients for gel and liquid phases are 2.83 × 10−6 cm2s−1 and 2.36 × 10−12 cm2s−1, respectively, when the weight ratio of nanofiber is 2.5 %, confirming that the gel phase is the dominant conducting phase in MPGEs. The nanofiber-reinforced MPGEs show the highest electrochemical potential window of 4.6 V and excellent interfacial stability at 2.5 wt% of nanofiber concentrations. Nanofiber loaded MPGE also exhibits extreme non-flammability, which can be exposed to the flame for longer without burning. Being highly conductive with outstanding electrochemical, interfacial and flame retardant properties, the synthesized MPGEs could be a suitable candidate for next-generation energy-storing devices. [Display omitted]